Valuation Accuracy for Petrol Fillig Stations: A Conceptual Framework - Kasim, Rozilah; Mohd Khairulanis, Muhamad Khairul Amin (Research in Management of Technology and Business, 2025)
This paper focuses on the valuation of petrol filling stations, presenting a comprehensive framework that integrate divere valation approaches such as the income, cost and sales comparison methods. The framework emphasozes key factors, including operational efficiecy, locational attribtes, and market dynamic, aligning with evolvig industry trends such as the incorporatio of electric vehicle charging infrastructure. The primary objectives are to enhance valuation accuracy and provide actionable insights for both researchers and industry practitioners. While the framework offers significant theoretical advancemets by addressing limitations inherent in traditional models, such as their neglect of intangible factors, it remains theoretical and requires empirical validation. The findings hold substantial implications for researchers aiming to refine valuation methodologies and for practitioners seeking to the advancement of valuation practices, fostering consistency and sustainability in both academic and professional contexts.